Remote Ischemic Preconditioning Has No Short Term Effect on Blood Pressure, Heart Rate, and Arterial Stiffness in Healthy Young Adults - Müller, Jan; Taebling, Marius; Oberhoffer, Renate (Frontiers in Physiology, 2019)
Objective Remote ischemic preconditioning (RIPC) are short episodes of ischemia and reperfusion applied to remote tissue to trigger responses in a specific organ or cardiovascular bed. This study investigates whether RIPC has a short-term effect on blood pressure (BP), heart rate, and arterial stiffness. Patients and Methods From March 2018 to August 2018, we included 40 healthy volunteers (23 female, age 25.6 ± 2.8 years) into this single-blinded randomized-controlled crossover trial. After measuring BP, heart rate, and arterial stiffness in supine position participants were randomized into intervention or SHAM group. The intervention group then underwent a RIPC protocol (3 cycles of 5 min of 200 mmHg ischemia followed by 5 min reperfusion) at the thigh. The SHAM group followed the same protocol just on the upper arm with 40 mmHg pressure inflation. Directly after this 30-min procedure a reassessment of hemodynamic measures was conducted. Results There were no significant changes in all five outcome parameters when comparing the effect of RIPC to SHAM. In peripheral systolic BP the mean difference between groups was Δ1.14 ± 6.5 mmHg (p = 0.672), and for diastolic BP Δ−0.69 ± 4.5 mmHg (p = 0.507). Heart rate shoed a Δ−0.8 ± 4.7 beats/min (p = 0.397). Regarding arterial stiffness measures, there was also no significant improvements thru RIPC. The mean difference between RIPC and SHAM for central systolic BP was Δ0.40 ± 7.2 mmHg (p = 0.951) and for PWV Δ0.01 ± 0.26 m/s (p = 0.563). Conclusion This study could not find any short-term effects of RIPC on arterial stiffness, BP, and heart rate in a RCT in young healthy adults.